Nature of the immunoreactive neurophysins in ectopic vasopressin-producing oat cell carcinomas of the lung. Demonstration of a putative common precursor to vasopressin and neurophysin. - Yamaji, T (1981)
In an attempt to delineate the nature of the immunoreactive neurophysins in oat cell carcinomas of the lung with ectopic vasopressin production, tumor neurophysins were characterized by gel filtration and by electrophoresis. In all of the five tumor tissues, activities of both vasopressin and nicotine-stimulated neurophysin (NSN) determined by radioimmunoassay were demonstrated. A small amount of oxytocin as well as estrogen-stimulated neurophysin was detected in three of the tissues. When tissue extract was subjected to Sephadex G-50 gel filtration in 0.2 N acetic acid, the major portion of immunoreactive NSN emerged in the fractions corresponding to the molecular size of 10,000. The migration pattern of NSN in these fractions on electrophoresis was qualitatively the same as that of NSN extracted from human posterior pituitary glands. In addition to this major neurophysin, immunoreactive NSN with the molecular size of 20,000 was consistently demonstrated in three tumor extracts. This high molecular weight form of neurophysin represented 6.5--8.7% of total NSN immunoactivities in each tumor extract and its elution profile was not changed when analyzed under denaturating conditions in 6 M guanidine hydrochloride. On electrophoresis, it migrated near the gamma globulin region; however, the peak was broad suggesting that it consists of more than two different molecular populations. A substantial portion of the high molecular weight NSN appears to be a glycoprotein judging from its binding to concanavalin A. When the high molecular weight from of neurophysin was incubated with trypsin, essentially all of the activities were converted into NSN with the molecular size of 10,000. Moreover, an equimolar amount of vasopressin was liberated after the treatment, the elution pattern of which closely resembled that of synthetic arginine vasopressin. When a lower concentration of trypsin was used, some of the 20,000-dalton neurophysin exhibited activities of both NSN and vasopressin. Since the antivasopressin serum used in this study appeared to be directed toward the ring portion side of vasopressin, these results suggest that this 20,000-dalton neurophysin is, in all probability, a common precursor to vasopressin and neurophysin, and that vasopressin may be located in the middle of the precursor molecule.